Code of corporate governance : impediments to compliance. - Liang, Michelle Shiying. (2008)
The aim of this paper is to provide readers with an overview of some of the practical impediments that listed Singapore-incorporated companies face in complying with the Singapore’s Code of Corporate Governance. Additionally, discussions and recommendations that seek to improve the compliance level will be presented.